2017
DOI: 10.12962/j25807471.v1i1.2183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Asymmetric Geometry on the Flexibility of Stent

Abstract: Mechanical characteristic assessment of the new stent design is important to improve the performance during the stenting process. Stent with good performance in geometric assessment should pass several tests in the unexpanded and expanded condition. The FEM assessment is expected to replace the actual mechanical assessment to save the cost and time of the manufacturing. In this study, the FEM assessment is conducted using the structural nonlinear analyses in ANSYS R15.0. The stent type used in the simulation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…However, the geometries of struts have less effect on the flexibility and the links have more effect on the flexibility. The parameter of the links plays a more important role in the flexibility of the stent [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the geometries of struts have less effect on the flexibility and the links have more effect on the flexibility. The parameter of the links plays a more important role in the flexibility of the stent [8].…”
Section: Discussionmentioning
confidence: 99%
“…Ju et al [7] found that link geometry had a significant effect on the bending behavior of stents. Syaifudin et al [8] found that asymmetric stents are less flexible that sinusoidal stents in their unexpanded configurations. Bobel et al [9] selected three physical stent geometries for comparative study and established the relationship between radial strength, flexibility, and longitudinal resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Setelah semua komponen dipasangkan pada tangan prostektik, selanjutnya melakukan pemrograman pada Arduino agar tangan dapat bergerak. Penggerakan jari-jari dilakukan dengan memberikan sinyal pada servo [10]. Servo diberikan sinyal putaran dengan sudut 90° [11].…”
Section: Proses Cetak Tangan Prostetikunclassified